Control and increase of economic efficiency of remote service of the enterprise in the services market in conditions of digitalization synergy - Datsenko, Ganna; Hladii, Iryna; Maister, Liudmyla; Kuznetsova, Svitlana; Bogatska, Nataliia (Pontificia Universidade Católica de São Paulo (PUCSP), 2025)
The article analyzes modern distance learning technologies, identifies the main trends in the development of distance learning and its role in solving the company's strategic problems, substantiates the advantages and disadvantages of modern distance learning technologies, substantiates the problems of modern distance learning technologies in the world; determines the procedure for constructing a balanced scorecard, develops a methodology for assessing the impact of distance learning system implementation based on the created balanced scorecard system of the company; determines the effectiveness of the current service based on the calculation of expenses for the distance learning system; compares the total cost of ownership when implementing a distance learning system; establishes sources of income received from a functioning distance learning system; determines the number of licenses purchased when implementing a distance learning system; develops a model for calculating the economic efficiency of the current work of an already used distance learning system, conducts dynamic modeling of the company's strategy for determining the number of clients connected to the distance learning system, develops practical recommendations for a financially optimal strategy for purchasing a remote service system; determines the advantages and disadvantages of distance learning system selection algorithms, classifies typical tasks for developing new algorithms without disadvantages; to develop a methodology for selecting a RSS for each category of companies and to build an algorithm for deciding on the implementation of a RSS using the method of calculating economic efficiency; an algorithm for constructing a decision on the implementation of a RSS using the method of calculating comparative economic efficiency has been developed; an algorithm for constructing a decision on the implementation of a RSS using the method of calculating boundary conditions has been developed.
Keywords: economic efficiency; services market; remote service; enterprises